Assessing the potential of the 2030 Agenda and the SDGs for reducing inequalities in Latin America - Gocłowska-Bolek, Joanna (Research Papers of Wrocław University of Economics, 2018)
Latin American economies have historically been defined by serious structural heterogeneity which is largely responsible for the high levels of social inequality. Social inequality is seen as a fundamental obstacle to sustainable development in the region. A commitment assumed by all the countries of the region, reflected in their willingness to accomplish the Goals of the 2030 Agenda for Sustainable Development, is that significantly reducing inequality is one of the main challenges that the region faces. In the article the author will examine the approach to inequality expressed in the Agenda 2030, especially in the SDG 10. The multidimensional inequality phenomena will be referred to, with the special focus on Latin America. Some of the axes and aspects of social inequality will be addressed to, drawing attention to what solutions are proposed by the Agenda 2030. Recent trends in reducing inequality in Latin America will also be analysed
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2018, Nr 510, s. 49-66
Keywords: Agenda 2030; SDGs; Latin American; inequality; social development; SDG; Ameryka Łacińska; nierówności społeczne; rozwój społeczny